Plan estratégico para la asociación de servicios de alimentación y limpieza manos activas "ASOSERMAC" del cantón Macará periodo 2023- 2030. - Trelles Piedra, Andrea Salomé (2024)
Currently, the Association of Food and Cleaning Services Manos Activas (ASOSERMAC), located in the canton of Macará, province of Loja, faces the challenge of improving its competitiveness and sustainability in an increasingly demanding market. For this reason, this Graduation Project focuses on the creation of a strategic plan for the period 2023- 2030, with the aim of optimizing the internal management of the association and ensuring its growth. Through a thorough diagnosis of the current situation, the organization’s strengths, weaknesses, opportunities, and threats were identified. Based on these results, key strategies were designed to improve the quality of services offered, diversify the range of products and services, and strengthen customer service. Likewise, the plan included the formulation of long-term strategic objectives to guide the association’s development in a structured manner, along with the creation of a detailed action plan with indicators to continuously evaluate the progress of these strategies’ implementation, ensuring that operational and administrative decisions are data-driven. The results project sustainable growth for ASOSERMAC, provided operational improvements are integrated and digital marketing strategies are implemented to attract and retain new customers. In summary, this strategic plan is designed to guide the association toward greater competitiveness, ensuring customer satisfaction and its consolidation in the local market.